The impact of sports experience on manual dexterity performances in school-age children - Antonino Patti; Domenico Savio Salvatore Vicari; Valerio Giustino; Flavia Figlioli; Genny Margherita Seidita; Alessandra Calogera Montalto Monella; Aurora Oddo; Antonio Paoli; Patrik Drid; Ewan Thomas; Antonino Bianco (Heliyon)
Background: Manual dexterity is the ability to manipulate objects with precision and efficiency, using hands and fingers to achieve a specific objective. This study investigated how the practice of Capoeira, a sport that stimulates coordination skills, affects manual dexterity in children regularly engaged in physical activity or in sedentary children. Methods: Eighty-four participants were enrolled in this study, including forty-six males and thirty-eight females (age: 8.52 ± 1.52 years). They were divided into three groups: the Capoeira Group (n = 13), the Physical Activity Group (n = 30), and the Control Group (n = 41). Each participant completed a manual dexterity test (n = 5 trials) and the same test in dual-task (n = 2 trials) using the Grooved Pegboard Test (GPT). Results: The five trials (GPT1 to GPT5) showed a decrease in the time to complete the test by the participants. The between-group variance in the finger-tapping test (GPT-FTT) and the counting test (GPT-CT) showed significant differences between groups (<0.001). Conclusion: Our results indicate that children who practiced physical activity and Capoeira had higher levels of manual dexterity compared to those of the control group. This study indicates that structured sports, such as Capoeira, can have a beneficial impact on improving manual dexterity. Considering these findings, schools should support the development of fine motor coordination through physical activity programs that emphasize coordination tasks, such as Capoeira.